(untitled) (mathematica didactica, 2025)
The increasingly widespread use of algorithmic decision-making systems has social implications that responsible citizens should understand. In this article, the ability to reflect in particular is seen as an important foundation for developing a corresponding algorithmic literacy as part of data literacy. The aim of this article is to characterize students’ reflections on the topic on an empirical basis in order to specify the professionalization content for prospective mathematics teachers more precisely.